Penguatan Peran Kepolisian Dalam Upaya Pencegahan Kekerasan Seksual Terhadap Anak Dan Perempuan - Abdurrachman, Hamidah; Sudewo, Fajar Ari; Dian Aryani, Fajar; Aditya Pratama, Erwin (Diktum: Jurnal Ilmu Hukum, 2022)
The role of the Police in handling cases of sexual violence against children and women through the PPA Unit is quite strategic in providing services and legal protection for women and children. The Minister of Women's Empowerment and Child Protection did not deny that the Indonesian National Police is the frontline in efforts to break the chain of violence against women and children. This research uses conceptual research methods. The results showed that there is a need for a comprehensive handling mechanism from the root of the problem until the victim gets justice and the perpetrator becomes a deterrent. efficiency and effectiveness of service. In handling women and children victims of violence, a quick and appropriate response is needed for victim services. Services for victims of violence should be prioritized and should not drag on in terms of administration and procedures. Second, the provision of services with a victim perspective. If so far the PPA Unit can be said to be moving in the phase after the occurrence of violence against children and women, in the sense of carrying out the law enforcement process while protecting victims, this activity seeks to provide strengthening and assistance downstream, namely when crime occurs, by early detection of potential violence in the region and providing education to the community to jointly carry out efforts to protect children and women from all forms of violence.